Silica-supported nickel based catalysts for bio-alcohol dry reforming (2005–2025): A two-decade bibliometric map and roadmap to net-zero hydrogen - Liew, Wei Man; Nurul Aini, Razali; Rohayu, Jusoh (Elsevier Ltd, 2025)
Silica-supported nickel (Ni/SiO2) catalysts represent a cost-effective route for low-carbon hydrogen production via the dry reforming of bio-alcohols, yet a broad perspective of the field's evolution and current performance limits remains incomplete. This review incorporates a 20-year bibliometric survey (2005–2025) with critical catalyst assessment, using VOSviewer and Biblioshiny to map development of knowledge and technological progress from 501 Scopus records. China leads in research output and collaboration, with Malaysia, Saudi Arabia, and the United States contributing to catalyst engineering and mechanistic modeling. Three main themes emerge: CO2 utilization, catalyst stability, and syngas optimization. Advanced Ni/SiO2 system includes MgO- or CeO2-modified composites, SBA-15 or KIT-6 frameworks, and Ag-, Re-, or Dy-promoted bimetallics, achieving over 60 % H2 yield and 70 % coke suppression. Key challenges persist in field of long-term stability and thorough techno-economic evaluation. A strategic roadmap coupling redox-active promoters, hierarchical porosity, and AI-guided screening is proposed to advance industrial readiness.